First record of Megaraptora (Theropoda, Neovenatoridae) from Brazil - Méndez, Ariel Hernán (2012)
An isolated caudal vertebral centrum of a theropod dinosaur was discovered in the Bauru Basin (Late Cretaceous) of Brazil, in the Maastrichtian São José do Rio Preto Formation. The vertebral centrum has pneumatic features that are similar to those in the megaraptoran theropods Aerosteon, Megaraptor, and Orkoraptor. For example, all these taxa share with the caudal centrum here described the presence of true pleurocoels or pneumatic foramina, immersed within a depression or fossa. Thus, the specimen is considered the first record of Megaraptora in Brazil. The present analysis provides new information on the vertebral caudal anatomy of this clade of bizarre Cretaceous theropods.